Examining the Association Between Co-Occurring Disorders and Seriousness of Misconduct by Female Prison Inmates. (May 2014) - Houser, Kimberly A.; Welsh, Wayne
Although studies have consistently demonstrated mentally ill offenders to be disproportionately involved in misconduct within correctional facilities, research is limited on the potential exacerbating effects of co-occurring disorders (CODs) on inmate behavior. With the vast number of offenders who have comorbid psychiatric and substance use disorders, it is essential that we understand whether the clinically interactive nature of CODs may present increased security and management challenges for correctional administrators. Using data from the Pennsylvania Department of Corrections (PADOC), we compared the institutional misconduct experiences of female inmates with CODs to those for inmates with singular disorders or no disorders. The findings of our study support prior research showing mental illness as a risk factor for prison misconduct. The results further suggest that the presence of both a substance use disorder and a mental illness exacerbates the risk of negative behaviors beyond the singular disorder of mental illness.